(untitled) (Fiep Bulletin - online, 2016)
This study is an academic research project, designed to meet the requirement of completion of the Postgraduate Course in Sports Management, offered by the College Claretian - University Center. The study aims to bring the awareness of society about the importance of physical education professional in the organization and realization of Sporting Events in the Social Sector, project carried out in the sports court of the State School Placido de Castro, in Jaru inside of Rondônia, in the year 2015. Accordingly, the execution of this project is to show, through concrete actions, the importance of physical education professional in organizing sporting events providing interaction between the low and upper classes, through sport. It is concluded as soon as the event’s harmony was due to some basic fundamentals of management: planning, organization, achievement, leadership, that those pleas were sent in search of the goals set and achieved.